2021
DOI: 10.31235/osf.io/zr7p3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why Do Homogeneous Friendships Persist in a Diverse Population? Making Sense of Homophily

Abstract: Homophily is one of the robust findings in social network studies. It persists even in a diverse population where the opportunity to develop homogeneous friendship is not greater than a mere chance and the process of developing heterogeneous friendship is facilitated. In this study, we introduce the Framework for Intergroup Relations and Multiple Affiliations Networks (FIRMAN), derived from social identity theory and social network framework, that can explain why that is the case. We begin by explaining its co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Further research might be able to recover the weights of each factor on US Twitter users' decisions to include or not include pronoun lists and to form or not form ties with others who do. Theory 1 might be tested experimentally or with agent-based modelling just as racial segregation in tie formation has (Firmansyah & Pratama, 2021;Wimmer & Lewis, 2010). We have demonstrated that other affiliations besides sexual or gender identity co-occur alongside pronoun lists.…”
Section: Discussionmentioning
confidence: 98%
“…Further research might be able to recover the weights of each factor on US Twitter users' decisions to include or not include pronoun lists and to form or not form ties with others who do. Theory 1 might be tested experimentally or with agent-based modelling just as racial segregation in tie formation has (Firmansyah & Pratama, 2021;Wimmer & Lewis, 2010). We have demonstrated that other affiliations besides sexual or gender identity co-occur alongside pronoun lists.…”
Section: Discussionmentioning
confidence: 98%
“…Theoretical Framework: Framework for Intergroup Relations and Multiple Affiliations Networks (FIRMAN) FIRMAN (Firmansyah & Pratama, 2021) is a formal theoretical framework in which individuals or agents are represented as nodes (with specified coordinates) and their relationships as ties (with specified lengths) in social identity spaces. A social identity space is an abstract space constituted by n numbers of social identities derived from the groups to which the individuals belong (e.g., gender, ethnicity, and sports clubs).…”
Section: Methodsmentioning
confidence: 99%
“…With the individuals located in the social identity space, we can easily calculate their social identity distance (w_dist) representing similarity/dissimilarity between any pair of nodes using equation (1), which is derived from Manhattan distance (Black, 2019). Social identity distance differs from Borgadus' social distance that is used to assess individuals' subjective acceptance of outgroup members as alters (Firmansyah & Pratama, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations